Efficacy and safety of aspirin in patients with peripheral vascular disease: An updated systematic review and meta-analysis of randomized controlled trials - Mahmoud, Ahmed N.; Elgendy, Akram Y.; Rambarat, Cecil; Mahtta, Dhruv; Elgendy, Islam Y.; Bavry, Anthony A. (PLOS ONE, 2017)
Background Although considered a cornerstone therapy, the efficacy and safety of aspirin for prevention of ischemic events in patients with peripheral vascular disease (PVD) remains uncertain. Thus, we aimed to evaluate aspirin use in both symptomatic and asymptomatic patients with PVD. Methods An electronic search of databases was conducted from inception until January 2017 for all randomized trials comparing aspirin with either placebo or control (no aspirin) in patients with PVD. The primary efficacy outcome was all-cause mortality, and the primary safety outcome was major bleeding. Other outcomes of interest were major adverse cardiac and cerebrovascular events (MACCE), myocardial infarction (MI), stroke and intracranial hemorrhage. Random-effects summary risk ratios (RR) were calculated using Der-Simonian and Liard model. The quality of evidence was assessed by GRADE tool and Cochrane risk of bias assessment tool. Results A total of 6,560 patients from 11 trials were included. Only two trials were considered to have low risk of bias. Compared with control, aspirin was associated with similar incidence of all-cause mortality (RR = 0.93, 95% confidence interval [CI] 0.8–1.1), MACCE (RR = 1.0, 95% CI 0.83–1.20), MI (RR = 0.91, 95% CI 0.67–1.23) and stroke (RR = 0.72, 95% CI 0.43–1.22), major bleeding (RR = 1.59, 95% CI 0.96–2.62) and intracranial hemorrhage (RR = 1.38, 95% CI 0.59–3.21). Conclusions Aspirin use in PVD might not be associated with improved cardiovascular outcomes or worse bleeding outcomes. Larger randomized trials assessing the efficacy and safety of aspirin in the contemporary era are mandatory to confirm the current findings. Guideline recommendations regarding the use of aspirin among patients with PVD need to be updated.